Design Of Multiband Microstrp Antenna On Cubesat For Ads-B Communication - Putra, Naufal Alim Harya; N, Bambang Setia; Edwar, Edwar (eProceedings of Engineering, 2023)
Automatic Dependent Surveillance-Broadcast(ADS-B) is a new technology in aircraft observation that uses theglobal positioning system (GPS) to track the position, speed, winddirection and altitude of the aircraft. The research aims tocompare the results of application simulations and the results offield measurements. ADSB simulation results return loss -21.13dB, VSWR 1.2181, gain 0.5 dBi, and axial ratio 3.06. S-Bandantenna simulation, return loss of -15.35 dB, VSWR of 3.89, gainof 3.88 dBi, and axial ratio of 9.7 dB. The measurement resultsobtained for the ADS-B antenna return loss -19.376 dB, VSWR1.25, gain 2.67 dBi, and axial ratio 1.341 dB. Measurement of theS-Band antenna return loss is -15.36 dB, VSWR is 1.35, gain is0.62 dBi and axial ratio is 1.33 dB. In the simulation andmeasurement of the ADS-B antenna, a close value is obtained. Inthe simulation and measurement of the S-Band antenna, there aredifferences in the measurement frequency from 300 MHz to 2700MHz, while in the simulation it is 2400 MHz. The factor thataffects the difference in results is the material used is not the sameas the material used in the simulation.Keywords: ADS-B, S-Band, Microstrip Antenna, CubeSat